2006
DOI: 10.1029/2005ja011396
|View full text |Cite
|
Sign up to set email alerts
|

On the chaotic nature of solar‐terrestrial environment: Interplanetary Alfvén intermittency

Abstract: [1] We present an overview of observational and theoretical evidence of chaos and intermittency in the solar-terrestrial environment including solar dynamo, solar atmosphere, solar wind, and terrestrial magnetosphere-ionosphere-atmosphere. The chaotic nature of space plasmas is studied by a nonlinear model of Alfvén waves described by the low-dimensional limit of the derivative nonlinear Schrödinger equation given by its stationary solutions in the frame moving with the driver wave velocity. A periodic window … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 110 publications
(144 reference statements)
1
22
0
Order By: Relevance
“…In particular, in agreement with other studies, we confirm the universal shape of the multifractal spectrum as noticed, e.g., by Burlaga (2001). Since the Cantor set is sensitive to initial conditions the multifractal spectrum for intermittent turbulence can be naturally related to the Lyapunov spectrum as discussed by Chian et al (2006). We have also calculated the degree of multifractality given in Eq.…”
Section: Resultssupporting
confidence: 75%
“…In particular, in agreement with other studies, we confirm the universal shape of the multifractal spectrum as noticed, e.g., by Burlaga (2001). Since the Cantor set is sensitive to initial conditions the multifractal spectrum for intermittent turbulence can be naturally related to the Lyapunov spectrum as discussed by Chian et al (2006). We have also calculated the degree of multifractality given in Eq.…”
Section: Resultssupporting
confidence: 75%
“…Numerical simulations of nonlinear plasma waves have confirmed that intermittent events are localized regions of plasmas (or fluids) governed by bursts of energy spikes (phase coherent structures) where phase synchronization is operating (He andChian, 2003, 2005). Since large-amplitude coherent structures of small scales have typical lifetimes longer than that of small-amplitude incoherent (stochastic) fluctuations, the dynamics of an intermittent turbulence, ubiquitous in the heliophysical environment (Chian et al, 2006), is dominated by coherent structures resulting from phase synchronization.…”
Section: Resultsmentioning
confidence: 93%
“…While the Alfvénic fluctuations are geoeffective at the solar minimum phase, the magnetic structures play a role at the solar maximum phase. Chian et al (2006) among others, also suggested that a close correlation between interplanetary Alfvén waves and AE index exists.…”
Section: Introductionmentioning
confidence: 99%